El proceso ante la corte interamericana de derechos humanos - Sánchez Sánchez, Alejandro (Universidad de Costa Rica - Colegio de Abogados y Abogadas de Costa Rica, 2018)
In present times, legal science has a great responsibility to the exercise of human rights in the Inter American Human Rights System because the procedural law of both the Commission and the Inter American Court of Human Rights should be analyzed to provide appropriate ideas and objectives to strengthen the national and international procedure. The purpose of this is that the specific cases submitted to those instances may reach the stage of sentence and execution to, therefore, crystallize the human rights of the governed, to finally reach international welfare within a framework of conventional coexistence.